2016
DOI: 10.1177/1049909116660276
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Reducing Hospital Readmission Rates: The Role of Hospice and Palliative Care

Abstract: National efforts to reduce rehospitalizations may result in improved integration of hospice and palliative care for patients who are at risk of readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…To the extent that systems can be developed to better understand patient goals of care upstream, 35 before the acute event occurs, as well as during timesensitive situations, these systems could apply across specialties to improve hospital-wide outcomes. 40,41 Limitations Findings should be interpreted in light of several limitations. First, this study focused on a subset of participants at 5 of the 10 hospitals in the LSL study.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that systems can be developed to better understand patient goals of care upstream, 35 before the acute event occurs, as well as during timesensitive situations, these systems could apply across specialties to improve hospital-wide outcomes. 40,41 Limitations Findings should be interpreted in light of several limitations. First, this study focused on a subset of participants at 5 of the 10 hospitals in the LSL study.…”
Section: Discussionmentioning
confidence: 99%
“…Policy intervention involved activities undertaken to align policy changes with clinical goals, priorities and patient outcomes Amin et al, 2014;Back et al, 2017;Barbash et al, 2017;Cherlin et al, 2017;Coleman et al, 2007;Duckers et al, 2009b;Gasparini et al, 2015;Iorio et al, 2016;Jurkowski et al, 2016;Ketko et al, 2015;Lanese, 2016;McClain et al, 2017;McHugh et al, 2011;Morrow et al, 2012;Padula et al, 2015;Russ et al, 2015;Sautter et al, 2007;Som, 2007;Stone et al, 2015;Wald et al, 2012;Weeks et al, 2014;Wiig et al, 2013;Yelland et al, 2017;Yu et al, 2...…”
Section: Goalsmentioning
confidence: 99%
“…Policy interventions could also be supported by internal infrastructure. In such examples implementation processes and tools, such as checklists or guidelines, were utilised or newly established within an individual hospital to support local implementation and drive required changes (Altman, 2012;Bates et al, 2014;Calikoglu et al, 2012;Cherlin et al, 2017;Iorio, 2015;Jurkowski et al, 2016;Lambert et al, 2015;Nisly et al, 2013;Padula et al, 2015;Sautter et al, 2007;Tung and Yang, 2009). When new processes or tools were developed this often required the allocation of additional resources and, in some cases, the establishment of new roles to directly support clinical practice changes (Altman, 2012;Iorio, 2015;Iorio et al, 2016;Kahin et al, 2017;Kodal et al, 2012;Kurtzman et al, 2011;Lanese, 2016;Morrow et al, 2012;Padula et al, 2015;Purvis et al, 2017;Resar et al, 2011;Wiig et al, 2013;Yu et al, 2017).…”
Section: Theme 2: Policy Intervention Is Supported By Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…A study was done among college students to measure the awareness of hospice care and services in Saudi Arabia. The study revealed that 74 (86.05%) of 86 Saudi Arabian students attending a Mid-Western public university did not know what hospice care is, and only 12 (13.95%) of 86 Saudi Arabian students had some knowledge about hospice care [16].…”
Section: Discussionmentioning
confidence: 96%